STUDY AND DESIGN OF DIGITAL MEDIA FORMATS FOR PUBLIC RELATIONS FOR SECONDARY CITY TOURISM NAKHON SI THAMMARAT PROVINCE - Boongerd, Parichart; Louhapensang, Chaturong; Piromgarn, Thanate (Journal of Industrial Education, 2021)
The objective of the study and design of digital media format for tourism public relations in the secondary city of Nakhon Si Thammarat is to study digital media formats, design the digital media, and assess the satisfaction of digital media consumers. For this study, digital media formats were divided into 60 forms with the experts’ analysis on the correlation for the digital media design. The correlation results were found that there were web production, digital publications, and digital media. With the human perception, there was 75 percent of the visual interest. Interesting of cultural identity and transcribing history, there were surveyed from the three raised weaving communities. The creation of the digital patterns from the raised cloth pattern was reflected the cultural identity classify patterns into groups, plants, animals, geometric, and miscellaneous patterns using Adobe Illustrator for modern and unique design. The design results were found that the model 1 was a high level of opinion ( = 4.39, S.D. = 0.37). Overall consumer satisfaction with digital aesthetics was ( = 4.57, S.D. = 0.63). Digital media was unique ( = 4.47, S.D. = 0.63). Digital media were suitable for use at ( = 4.63, S.D. = 0.49). The price was suitable for digital media formats (products) ( = 4.43, S.D. = 0.77). The price was reasonable when compared to the quality (products) ( = 4.40, S.D. = 0.56). The price was reasonable when compared to the features (products) ( = 4.33, S.D. = 0.61). Distribution channels on digital media formats can be sold at the trading fairs (products) and at an online (products) ( = 4.60, S.D. = 0.56). At the marketing promotion, there was a digital media format delivery service (products) ( = 4.40, S.D. = 0.67). There were various forms of public relations in digital media ( = 4.53, S.D. = 0.57) and an incentive to purchase different forms of digital media ( = 4.40, S.D. = 0.81).